NIGERIA IN THE QUEST FOR A NATIONAL IDENTITY - Omenukor, Donald Uchenna (African Journal of Social and Behavioural Sciences, 2024)
This paper examined the issue of Nigeria’s national identity. The paper identified the problem of the lack of a positive national identity for Nigeria and Nigerians. This lack of a positive national identity is the product of a derailed national agenda for development. National identity is a very important factor in the development of any nation and in the way outsiders perceive the nation and her people. This national identity could be developed from such things as national symbols and anthems. However, the problem remains that Nigeria as a country has failed to leverage a number of her natural and nurtured features, to develop a positive self-image that would give rise to a positive national identity. Adopting the method of content analysis, the paper concludes that the present image of Nigeria is one drawn from some negative narratives; narratives that are the products of failed aspirations. For the country to be able to develop a positive national identity, the narratives must change.